Return of the Gar - Spitzer, Mark, 1965- (Book collections on Project MUSE., 2015)
The alligator gar belongs to a family of fish that has remained fundamentally unchanged since the Cretaceous, over 100 million years ago. Its intimidating size and plethora of teeth have made it demonized throughout its range in North America, resulting in needless killing. Massive oil spills in its breeding range have not helped its population either. Interspersing science, folklore, history, and action-packed fishing narratives, Spitzer's empathy for and fascination with this air-breathing, armored fish provides for an entertaining odyssey that examines management efforts to preserve and pro.